Pengaruh Struktur Aset, Profitabilitas dan Ukuran Perusahaan terhadap Struktur Modal : (Studi Kasus pada Sub Sektor Barang Konsumsi Non Cyclical 2019 -2022) - Budiarti, Dinar; Kinasih, Hayu Wikan; Pratiwi, Ririh Dian; Prajanto, Agung (Politeknik Negeri Ambon, 2024)
Business growth and production expansion are basically the basis for companies to seek sources of income for their capital. This research aims to obtain empirical evidence and test related to how asset structure, profitability, and company size influence capital structure. By involving non-cyclical consumption sub-sector companies for 2019 - 2022 and registered on the IDX, 111 data were obtained using the purposive sampling method. The data analysis technique used is multiple linear regression with Spss 26. The research results show that asset structure and company size have a effect on capital structure. Meanwhile, the profitability variable has no effect on capital structure. The low adjusted r square in this study makes it have to be reviewed with other variables. The results showed that the companies taken preferred the use of external funds, namely debt. Keywords : Capital Structure, Asset Structure, Profitability, and Company Size.